The unmet needs among working mothers of children with epilepsy attending specialist hospitals in Kelantan: a mixed methods study - Abdullah, Noor Aida (2024)
Background: Working mothers of children with epilepsy (CWE) face a range of unmet needs and challenges that may impact their health and well-being. These unmet needs occur when assistance or support to perform everyday activities is not provided. The unpredictable nature of epilepsy causes severe work-family conflict among these women, potentially resulting in higher levels of unmet needs, which can further exacerbate the difficulties they encounter. Objective: The objectives of this study were to identify the unmet needs among working mothers of CWE, its predictive factors, and the barriers leading to unmet needs. Methodology: This was a mixed-method study involving a combination of quantitative (Phase 1) and qualitative methods (Phase 2) from February till August 2023. Phase 1 study involved 204 working mothers of CWE registered at the Paediatric Neurology Clinic in Kelantan, while Phase 2 involved 15 working mothers from Phase 1 who agreed to be interviewed. The validated Malay version of Family Needs Survey questionnaire was used to assess the unmet needs. General linear regression was applied to analyse the relationship between unmet needs scores and study factors. Thematic analysis was used to assess the barrier leading to unmet needs among the mothers. Result: The quantitative study found the highest prevalence of unmet needs was observed in the community services domain (81.6%), followed by the information domain (71.9%), social support domain (53.1%), financial domain (43.2%), and explaining to others domain (28.9%). The lowest unmet need was observed for the family functioning domain (28.4%). Several factors were significantly related to higher unmet needs, including seeking follow-up care at secondary hospitals, having children with comorbidities, working in the government sector, and being employed on a contract basis. On the other hand, factors that reduced unmet needs included belonging to a nuclear family structure and having full-time employment. The findings from the quantitative component informed the design and focus of the subsequent qualitative exploration. The qualitative phase identified three main themes related to the barriers faced by working mothers of CWE. These themes centred on the child; “Uncertainty and endless worrying for my child”, the mother; “Me and my career”, and the surrounding circumstances; “I don’t receive enough support”. Mothers expressed constant uncertainty and worry about their child's well-being. They also struggled with balancing their own needs and career aspirations. Additionally, challenges arose from family dynamics, government policies, and societal expectations. Conclusion: This study highlights the significant unmet needs among working mothers of CWE in Kelantan, emphasizing the profound impact on their daily lives and well-being. The highest unmet needs were found in community services and information, suggesting a critical gap in accessible support and resources. Factors such as seeking care at secondary hospitals, children's comorbidities, government sector employment, and contract-based work were associated with higher unmet needs, while nuclear family structure and full-time employment reduced these needs. Qualitative insights revealed persistent worry for their children, struggles in balancing personal needs and careers, and a lack of adequate support from family, government, and society. Addressing these unmet needs requires a multifaceted approach, including improved community services, information dissemination, and supportive policies to alleviate the burdens faced by these mothers.